A photoinitiator and its preparation method and application

By attaching unsaturated monomers to the surface of nano ZnO particles, the problems of poor dispersion stability and low photo conversion efficiency of nano ZnO photoinitiator are solved, and a more efficient and safe photoinitiator is achieved, which is suitable for industrial applications.

CN116217758BActive Publication Date: 2025-02-11SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310251369.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-02-11
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

As a photoinitiator, nano ZnO has problems such as poor dispersion stability, low photoconversion efficiency, short hydroxyl radical lifetime and limited diffusion distance, which is difficult to meet practical application requirements.

Method used

By adhering unsaturated monomers, such as methyl methacrylate, styrene, 1,6-hexanediol diacrylate and tripropylene glycol diacrylate, a stable photoinitiator is formed to enhance its Dispersion stability and photoconversion efficiency.

Benefits of technology

It significantly improves the dispersion stability and photoconversion efficiency of the photoinitiator, ensures its safety and efficiency in practical applications, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116217758B_ABST
    Figure CN116217758B_ABST
Patent Text Reader

Abstract

The present invention discloses a photoinitiator and a preparation method and application thereof. The composition of the photoinitiator of the present invention includes nano ZnO particles and unsaturated monomers attached to the surface of the nano ZnO particles, and the unsaturated monomers are at least one of methyl methacrylate, styrene, 1,6-hexanediol diacrylate, and tripropylene glycol diacrylate. The preparation method of the photoinitiator of the present invention comprises the following steps: dispersing a soluble zinc salt, a caustic alkali and an unsaturated monomer in ethanol, and then performing a solvent thermal reaction to obtain the photoinitiator. The photoinitiator of the present invention has the advantages of excellent dispersion stability, high light conversion efficiency, safety and non-toxicity, and its preparation process is simple, and is suitable for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoinitiators, and in particular to a photoinitiator and a preparation method and application thereof. Background Art

[0002] Photocurable coatings are mainly composed of photosensitive resins, photoinitiators and diluents. They have the advantages of short curing time (a few fractions of a second to a few minutes), low curing temperature, and low volatile content, and have very broad application prospects. The commonly used photoinitiators in photocurable coatings are organic photoinitiators, which usually cannot react completely. The residues and photolytic small molecules produced will diffuse and migrate, and eventually pollute the substrate and the environment. Nano ZnO has excellent photocatalytic activity and does not produce small molecular pollutants during photolysis. It can be used as a non-toxic photoinitiator. However, the surface energy of nano ZnO is very high, and the particles are easy to agglomerate. In addition, since the surface of nano ZnO contains hydroxyl groups, it is difficult to evenly disperse in the organic phase, which ultimately leads to poor dispersion stability, low photoconversion efficiency, short life of the generated hydroxyl free radicals, and limited diffusion distance of nano ZnO, making it difficult to fully meet the requirements of practical applications.

[0003] Therefore, it is of great significance to develop a photoinitiator with excellent dispersion stability, high photoconversion efficiency, safety and non-toxicity. Summary of the invention

[0004] The purpose of the present invention is to provide a photoinitiator and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is:

[0006] A photoinitiator comprises nano ZnO particles and unsaturated monomers attached to the surface of the nano ZnO particles; the unsaturated monomers are at least one of methyl methacrylate (MMA), styrene, 1,6-hexanediol diacrylate (HDDA) and tripropylene glycol diacrylate (TPGDA).

[0007] Preferably, the unsaturated monomer is tripropylene glycol diacrylate.

[0008] Preferably, the mass ratio of the nano ZnO particles to the unsaturated monomer is 1:0.01-0.06.

[0009] Preferably, the average particle size of the nano ZnO particles is 10 nm to 20 nm.

[0010] A method for preparing the photoinitiator as described above comprises the following steps: dispersing a soluble zinc salt, a caustic alkali and an unsaturated monomer in ethanol, and then performing a solvent thermal reaction to obtain the photoinitiator.

[0011] Preferably, a method for preparing the photoinitiator as described above comprises the following steps: dispersing a soluble zinc salt in ethanol, then dropwise adding an ethanol solution containing caustic soda and an unsaturated monomer, then performing a solvent thermal reaction, and then centrifuging, washing and drying to obtain the photoinitiator.

[0012] Preferably, the soluble zinc salt is at least one of zinc acetate, zinc nitrate and zinc chloride.

[0013] Preferably, the caustic alkali is at least one of sodium hydroxide and potassium hydroxide.

[0014] Preferably, the dropping time is 15 min to 30 min.

[0015] Preferably, the solvothermal reaction is carried out at 20°C to 90°C.

[0016] Preferably, the solvent thermal reaction time is 2h to 3h.

[0017] Preferably, the solvent thermal reaction is carried out under stirring, and the rotation speed of the stirrer is 150r / min to 250r / min.

[0018] Preferably, the centrifugation is carried out at a centrifuge speed of 8000 rpm to 12000 rpm, and the centrifugation time is 5 min to 15 min.

[0019] Preferably, the solvent used for the washing is ethanol.

[0020] Preferably, the drying is carried out at room temperature (25°C±5°C) for 20 hours to 30 hours.

[0021] A photocurable coating comprises the above-mentioned photoinitiator.

[0022] Preferably, the amount of the photoinitiator used is 0.1% to 6.0% of the mass of the base resin in the photocurable coating.

[0023] Preferably, the base resin is polyurethane acrylate.

[0024] The beneficial effects of the present invention are as follows: the photoinitiator of the present invention has the advantages of excellent dispersion stability, high light conversion efficiency, safety and non-toxicity, and the preparation process is simple, and is suitable for large-scale industrial application.

[0025] Specifically, the photoinitiator of the present invention is composed of nano ZnO particles and unsaturated monomers attached to the surface of the nano ZnO particles. The unsaturated monomers can not only prevent the agglomeration of the nano ZnO particles and improve their dispersion stability, but also enable the hydroxyl radicals generated by light (the nano ZnO particles will generate electrons and holes under the irradiation of ultraviolet light, and the electrons and holes will oxidize the hydroxyl groups and water molecules on the surface of the nano ZnO particles into hydrogen peroxide and hydroxyl radicals, etc., and the generated hydroxyl radicals can make the paint film photocured) to diffuse out quickly, thereby improving the light conversion efficiency. In addition, the nano ZnO particles can also act as fillers to improve the mechanical properties of the paint film. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the infrared absorption spectrum of the nano ZnO particles, TPGDA and photoinitiator in Example 4.

[0027] Figure 2 It is the SEM picture of the photoinitiator in comparative example and Example 4.

[0028] Figure 3 Graph showing the particle size distribution of the photoinitiator in the comparative example and Example 4.

[0029] Figure 4 The photoconversion rate-illumination time relationship curves of the photoinitiators in Examples 1 to 5, the photoinitiator in the comparative example, and the waterborne polyurethane acrylate are shown. DETAILED DESCRIPTION

[0030] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0031] Embodiment 1:

[0032] A photoinitiator, the preparation method of which comprises the following steps:

[0033] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide and 0.0032 g of tripropylene glycol diacrylate were dissolved in 20 mL of anhydrous ethanol at room temperature and added dropwise to the stirred zinc-containing solution. The addition was completed within 15 min, and the mixture was stirred at 40°C for 2 h. The mixture was allowed to stand and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0034] A photocurable coating, the preparation method of which comprises the following steps:

[0035] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0036] Embodiment 2:

[0037] A photoinitiator, the preparation method of which comprises the following steps:

[0038] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide and 0.0065 g of tripropylene glycol diacrylate were dissolved in 20 mL of anhydrous ethanol at room temperature and added dropwise to the stirred zinc-containing solution. The addition was completed within 15 min, and the mixture was stirred at 40°C for 2 h. The mixture was allowed to stand and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0039] A photocurable coating, the preparation method of which comprises the following steps:

[0040] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0041] Embodiment 3:

[0042] A photoinitiator, the preparation method of which comprises the following steps:

[0043] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide and 0.0130 g of tripropylene glycol diacrylate were dissolved in 20 mL of anhydrous ethanol at room temperature and added dropwise to the stirred zinc-containing solution. The addition was completed within 15 min, and the mixture was stirred at 40°C for 2 h. The mixture was allowed to stand and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0044] A photocurable coating, the preparation method of which comprises the following steps:

[0045] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0046] Embodiment 4:

[0047] A photoinitiator, the preparation method of which comprises the following steps:

[0048] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide and 0.0162 g of tripropylene glycol diacrylate were dissolved in 20 mL of anhydrous ethanol at room temperature and added dropwise to the stirred zinc-containing solution. The addition was completed within 15 min, and the mixture was stirred at 40°C for 2 h. The mixture was allowed to stand and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0049] A photocurable coating, the preparation method of which comprises the following steps:

[0050] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0051] Embodiment 5:

[0052] A photoinitiator, the preparation method of which comprises the following steps:

[0053] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide and 0.0194 g of tripropylene glycol diacrylate were dissolved in 20 mL of anhydrous ethanol at room temperature and added dropwise to the stirred zinc-containing solution. The addition was completed within 15 min, and the mixture was stirred at 40°C for 2 h. The mixture was allowed to stand and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0054] A photocurable coating, the preparation method of which comprises the following steps:

[0055] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0056] Comparative Example:

[0057] A photoinitiator, the preparation method of which comprises the following steps:

[0058] 1.0975 g of Zn(CH3COO)2·2H2O was added to 80 mL of anhydrous ethanol, and then stirred at 40°C for 1 h to prepare a zinc-containing solution. Then, 0.32 g of sodium hydroxide was dissolved in 20 mL of anhydrous ethanol at room temperature and then added dropwise to the stirred zinc-containing solution for 1 min. The mixture was stirred at 40°C for 2 h, allowed to stand, and then centrifuged at 10000 rpm for 10 min. The solid obtained by centrifugation was washed 3 times with anhydrous ethanol and dried at room temperature to obtain a photoinitiator.

[0059] A photocurable coating, the preparation method of which comprises the following steps:

[0060] 0.25 g of the above-mentioned photoinitiator was added into 5 g of waterborne polyurethane acrylate (solid content of 50%), and stirred evenly to obtain a photocurable coating.

[0061] Performance Test:

[0062] 1) The infrared absorption spectra of the nano ZnO particles, TPGDA (tripropylene glycol diacrylate) and the photoinitiator in Example 4 are as follows: Figure 1 shown.

[0063] Depend on Figure 1 It can be seen that the Zn-O absorption peak of nano ZnO particles is at 443 cm -1 At 3436cm -1 、1563cm -1 and 1407cm -1 The absorption peaks of the stretching vibration and bending vibration of the hydroxyl groups on the surface of the nano ZnO particles are at 1735 cm -1 、1612cm -1 and 1160cm -1 There are three characteristic peaks at the bottom, corresponding to the stretching vibration absorption peaks of C=O, C=C and COC in TPGDA, indicating that the modification of nano-ZnO particles by TPGDA was successfully achieved.

[0064] 2) The scanning electron microscope (SEM) images of the photoinitiators in the comparative example and Example 4 are as follows: Figure 2 (a and b are comparative examples, c and d are example 4), the particle size distribution diagram is as shown in Figure 3 (a is a comparative example, b is embodiment 4) as shown.

[0065] Depend on Figure 2 and Figure 3 It can be seen that the shapes of the photoinitiators in the comparative example and Example 4 are basically the same, both of which are approximately spherical; the average particle size of the photoinitiator in the comparative example is 49.71nm±9.39nm, while the average particle size of the photoinitiator in Example 4 is 14.69nm±2.50nm, and the particle size is much smaller. The reason is that TPGDA will prevent the growth of the particle size during the formation of ZnO particles (TPGDA on the surface of ZnO particles can improve the dispersibility of ZnO particles).

[0066] 3) The photoinitiators in Examples 1 to 5 and the photoinitiator in the comparative example were respectively mixed with waterborne polyurethane acrylate (solid content 50%) at a mass ratio of 0.05:1 to prepare a mixed solution, and then dropped on a potassium bromide sheet for real-time infrared testing (pure waterborne polyurethane acrylate was used as a reference). According to the wavelength of 810 cm-1 The light conversion rate was calculated by the change of the C=C absorption peak near the photoconversion rate, and the obtained light conversion rate-illumination time relationship curve was as follows: Figure 4 shown.

[0067] Note: The calculation formula for light conversion rate is: α(%)=(A0-A t ) / A0×100%, where A0 and A t The samples were tested at a wavelength of 810 cm before and after illumination. -1 C=C absorbance value nearby.

[0068] Depend on Figure 4 It can be seen that the photoconversion rate (double bond conversion rate) of the photoinitiator in Example 1 is the highest (36.19%), followed by Example 2 (31.57%) and Example 4 (31.02%), and the photoconversion rates of the photoinitiators in Examples 1 to 5 are all higher than those of the photoinitiators in the comparative examples.

[0069] 4) The photocurable coatings in Examples 1 to 5 and the comparative example were applied to the surfaces of the glass plate and the tinplate plate, respectively, and dried at room temperature for 30 min, then at 60°C for 1 h, and then at a light irradiance of 80 mw / cm 2 The coating was cured under a high-pressure mercury lamp for 90 seconds to form a photocured coating film, and then a performance test was performed (pure water-based polyurethane acrylate was used as a control). The test results are shown in Table 1. Referring to the photocurable coating in Example 4, the photocurable coating with different photocuring agent contents was obtained by adjusting the photocuring agent content (1wt%, 2wt%, 3wt%, 4wt%, 5wt% and 6wt%), and then cured to form a film to obtain a photocured coating film with different photocuring agent contents, and then a performance test was performed. The test results are shown in Table 2:

[0070] Table 1 Performance test results of light-cured coatings

[0071]

[0072]

[0073] Table 2 Performance test results of photocurable coatings with different photocuring agent contents

[0074]

[0075] Note:

[0076] Gloss: Refer to "GB / T 9754-2007 Determination of specular gloss of paint films without metallic pigments" and use WGG60 E4 gloss meter from Foshan Sanlian Keyi Ceramic Equipment Co., Ltd. to test the gloss of the light-cured coating on an ABS board. Take 5 measurements on the same sample and take the average value.

[0077] Hardness: Refer to "GB / T 6739-2006 Paint and varnish pencil method for determination of film hardness" and use BDG 506 / 2S pencil hardness tester from Guangzhou Biaogeda Laboratory Instruments and Supplies Co., Ltd. to test the pencil hardness of the light-cured coating by scratching the tinplate 5 times at a uniform speed.

[0078] Adhesion: Refer to "GB / T 9286-1998 Cross-cut Test for Paint and Varnish Films" and use BDG 502 paint film cross-cutting device from Guangzhou Biaogeda Laboratory Instruments and Supplies Co., Ltd. to test. Use the cross-cutting method to evenly scratch the tinplate horizontally and vertically once, stick 3M tape on the scratch and quickly pull it off to observe the shedding of the light-cured coating. The same sample is tested 3 times in parallel at different positions.

[0079] Water resistance: Refer to "GB / T 1733-1993 Determination of water resistance of paint film" and use the immersion method to test the water resistance of the light-cured coating. Specific operation: Soak the light-cured coating in deionized water for 24 hours, take it out, use filter paper to absorb the moisture on the surface of the paint film, and observe whether the paint film has bubbling, peeling, etc., and conduct 3 parallel tests.

[0080] Alkali resistance: refer to "GB / T 9265-2009 Determination of Alkali Resistance of Architectural Paint Coatings" and use the immersion method to test the alkali resistance of the light-cured coating. Specific operation: immerse the light-cured coating in a 50g / L sodium carbonate solution for 2h, take it out, use filter paper to absorb the moisture on the surface of the paint film, and observe whether the paint film has bubbling, peeling, etc. The test is carried out three times in parallel.

[0081] Impact resistance: Refer to "GB / T 1732-1993 Determination of impact resistance of paint film" and use BGD 304 paint film impactor of Guangzhou Biaogeda Laboratory Instruments and Supplies Co., Ltd. for testing. Specific operation: let a 1kg weight fall freely to impact the light-cured coating on the tinplate. The maximum height (cm) without causing damage to the paint film indicates the impact resistance of the paint film. The same sample is tested 3 times in parallel.

[0082] Water absorption rate: Cut the photocuring coating into a size of 2cm×2cm, weigh it, and record the mass as m0. Then soak it in deionized water for 24 hours, take it out, use filter paper to absorb the moisture on the surface of the paint film, weigh it, and record the mass as m1. The water absorption rate calculation formula is: Water absorption rate (%) = (m1-m0) / m0×100%.

[0083] Gel rate: Cut the photocured coating into a size of 2cm×2cm, weigh it, and record the mass as n0. Then put it into acetone and extract it with a Soxhlet extractor at 65°C for 6 hours. After taking out the paint film, place it in an oven at 60°C and dry it to constant weight. Weigh it and record the mass as n1. The gel rate calculation formula is: Gel rate (%) = n1 / n0×100%.

[0084] It can be seen from Table 1 and Table 2 that the photoinitiator of the present invention can significantly improve the hardness, adhesion, water resistance, impact resistance and light conversion rate of the photocurable paint film.

[0085] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A photoinitiator, characterized in that The composition comprises nano ZnO particles and unsaturated monomers attached to the surface of the nano ZnO particles; the unsaturated monomers are tripropylene glycol diacrylate; the mass ratio of the nano ZnO particles to the unsaturated monomers is 1:0.01-0.

06.

2. The photoinitiator according to claim 1, characterized in that: The average particle size of the nano ZnO particles is 10nm-20nm.

3. A method for preparing a photoinitiator as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: dispersing soluble zinc salt, caustic alkali and unsaturated monomer in ethanol, and then carrying out solvent thermal reaction to obtain a photoinitiator.

4. The preparation method according to claim 3, characterized in that: The soluble zinc salt is at least one of zinc acetate, zinc nitrate and zinc chloride; the caustic alkali is at least one of sodium hydroxide and potassium hydroxide.

5. The preparation method according to claim 3 or 4, characterized in that: The solvent thermal reaction is carried out at 20°C to 90°C.

6. The preparation method according to claim 5, characterized in that: The solvent thermal reaction time is 2h to 3h.

7. A photocurable coating, characterized in that: Contains the photoinitiator according to claim 1 or 2.

8. The photocurable coating according to claim 7, characterized in that: The amount of the photoinitiator used is 0.1% to 6.0% of the mass of the base resin in the photocurable coating.

9. The photocurable coating according to claim 8, characterized in that: The base resin is polyurethane acrylate.

Citation Information

Patent Citations

  • Polymethyl methacryate microsphere coating zinc oxide composite material and preparation thereof

    CN101475726A

  • Compound type odor-less light initiator and ultraviolet curing coating material

    CN106632741A